A Comparative Study of Overshot Flaking Between Clovis and Other Components From the Gault Site, Texas. (3rd April 2018) - Lassen, Robert
ABSTRACT: This study utilizes data from the Gault site (41BL323) to address intentionality in Clovis overshot flaking. Most research in recent decades considers overshot flakes a purposeful part of Clovis biface reduction. However, recent research by Eren et al. has questioned this interpretation, experimentally demonstrating that overshot flakes may represent failed attempts at removing large overface flakes. The present study compares overshot flake counts from Clovis and other components in Area 15, as well as comparing edge removal measurements from Clovis and non-Clovis overshots from Areas 8 and 15. Results indicate that overshots are proportionally more common in the Clovis component than in any other stratum, and Clovis overshot flakes consistently remove less mass from the opposite edge than those from other components. Therefore, it appears that overshots are removed more consistently and with more precision in Clovis than in any other component, making them more likely to be intentional.